INJEKSI KORTIKOSTEROID PADA SINDROMA TEROWONGAN KARPAL - Sekplin A. S. Sekeon; Agus S. Wijaya (Neurologi Manado, 2019)
Carpal tunnel syndrome is one of the most common compression neuropathies of the upper limbs. This syndrome is known primarily in occupational health, especially in industries where workers are involved in the use of repetitive hands and tools with strong vibrations. Symptoms may include pain or tingling in the distribution of the median nerve, weakness in grasping and other hand functions. Conservative management is given to patients with mild and moderate degrees, while in patients with severe stage, surgery is recommended. One of the most effective conservative therapies is Ultrasound-guided local injection of corticosteroids. It is a proven and effective treatment in reducing complaint, and can also delay the need for surgery.